Imaging in neurovascular disease a case-based approach - Brinjikji, Waleed (Thieme, 2019)
Unique case-based reference presents high-yield images and expertise focused on vascular neuroradiology. Imaging in Neurovascular Disease: A Case-Based Approach by Waleed Brinjikji and Timo Krings is unique in its approach, detailing diagnostic and interventional neuroradiology cases based on radiologic findings. The book explores the key role vascular imaging can play in treatment decision making, prognostication, and improving the understanding of the pathophysiology of neurovascular diseases. Spread over 11 chapters, this book covers a full spectrum of neurovascular diseases spanning the age continuum, starting with acute ischemic stroke, concluding with spinal vascular disease. All vascular neuroradiology cases follow a consistent format. After a succinct introduction describing the clinical scenario with relevant case images, the authors present key facts about the disease and the integral role of different neurovascular imaging procedures in disease management. Imaging findings are discussed in depth, with insightful clinical pearls on image-guided procedures and tips on managing potential pitfalls.